Determination of Majority Carrier Capture Rates via Deep Level Transient Spectroscopy. (1st January 2016) - Lauwaert, J.; Khelifi, S.; Vrielinck, H.
Abstract : In Deep Level Transient Spectroscopy (DLTS) experiments the majority carrier capture rate is often determined by observing the growth of the signal amplitude as a function of filling pulse duration at constant temperature. The analysis of such experiments is complicated by the phenomenon of slow capture: carrier capture by defects in the Debye tail of the depletion layer at the pulse voltage. We review here three approaches for analyzing isothermal pulse duration variation DLTS experiments that have been described or at least have been frequently used in literature. These methods are compared for their ability to correctly extract capture rates from simulated data as well as from actual experimental data for the Fe − /2 − level in crystalline germanium. Finally, we tested the performance of the three methods for analysis of DLTS signals that experience a delayed growth, modeled by an additional time constant in the system.